1992
DOI: 10.1523/jneurosci.12-08-02948.1992
|View full text |Cite
|
Sign up to set email alerts
|

Plasmalemmal insertion and modification of sodium channels at the nerve growth cone

Abstract: We have characterized voltage-dependent sodium channels in growth cones (GCPs) isolated from fetal rat brain using saxitoxin and TTX binding as well as recordings from channels reconstituted into lipid bilayer membranes. Both high- and low-affinity binding sites are present in GCP membranes. However, the two binding sites are segregated largely or completely, with the high-affinity binding sites in the plasmalemma, and the low-affinity sites in an internal membrane compartment. Plasmalemmal insertion of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…By analogy, synaptotagmin might therefore be involved in the trafficking and insertion of sodium channels in neurons. Consistent with this hypothesis, elevation of the intracellular Ca 2ϩ concentration in growth cones induced insertion of sodium channels at the cell surface (35).…”
Section: Discussionmentioning
confidence: 65%
“…By analogy, synaptotagmin might therefore be involved in the trafficking and insertion of sodium channels in neurons. Consistent with this hypothesis, elevation of the intracellular Ca 2ϩ concentration in growth cones induced insertion of sodium channels at the cell surface (35).…”
Section: Discussionmentioning
confidence: 65%
“…The apparent cytoplasmic distribution of rH1 protein in spinal cord astrocytes, in some cases limited to the perinuclear portion of the cytoplasm, is consistent with sequestration of rH1 protein, or of partially processed protein, within a cytoplasmic compartment such as the Golgi apparatus. There is evidence for the existence of a pool of intracellular Na ϩ channel ␣-subunits in neurons (Dargent et al, 1994;Schmidt and Catterall, 1986;Wonderlin and French, 1991;Wood et al, 1992Wood et al, , 1995 and Schwann cells (Ritchie et al, 1990). Perinuclear labeling of rat atrial and ventricular cells was also observed using rH1 and R-12 antibodies, identifying either nascent protein or cytoplasmic stores of protein available for transport to the surface membrane (Cohen, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Ca 2+ transients in the growth cone stimulate axon extension (Gu and Spitzer, 1995) and Ca 2+ transients in the filopodia induce growth cone turning (Gomez et al, 2001). The downstream actions of Ca 2+ in neurons include control of growth cone traction (Conklin et al, 2005), polymerization of cytoskeletal structural elements (Lautermilch and Spitzer, 2000) and membrane insertion at growth cones (Lockerbie et al, 1991;Wood et al, 1992), which have direct effects on neurite outgrowth behaviour. By creating local increases in [Ca 2+ ] i at growth cones, the neurite can be steered (Henley and Poo, 2004).…”
Section: +mentioning
confidence: 99%